The new rules of sales and Service - David Meerman Scott (Wiley, 2016)
DAVID MEERMAN SCOTT is the author of ten books including The New Rules of Marketing and PR, Marketing Lessons from the Grateful Dead, and Newsjacking. His books open people's eyes to the new realities of sales, marketing, and public relations. David's popular blog, advisory work with fast-growing companies, and hundreds of speaking engagements around the world give him a singular perspective on how businesses are reaching buyers directly and in real time.=541 ## Mua